Footnote

For those who know linear algebra and are interested, here is a sketch of the proof.

Let feature vector x have mean mx and covariance matrix Cx, and let feature vector y have mean my and covariance matrix Cy. If y = Ax, we know that my = Amx and Cy = A Cx A'. From this last expression, it follows that Cy-1 = A-1 ' Cx-1 A-1. Now consider

ry2 = ( y - my )' Cy-1 ( y - my )
= ( Ax - Amx )' ( A-1 ' Cx-1 A-1 ) ( Ax - A mx )

= ( x - mx )' A' A-1 ' Cx-1 A-1 A ( x - mx )

= ( x - mx )' (A-1 A)' Cx-1 (A-1 A) ( x - mx )

= ( x - mx )' Cx-1 ( x - mx )

= rx2 .
Up arrow Back